2020
DOI: 10.1016/j.annonc.2020.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Collateral damage: the impact on outcomes from cancer surgery of the COVID-19 pandemic

Abstract: A COVID19 lockdown in India posed signi cant challenges to the continuation of radiotherapy (RT) and systemic therapy services. While several COVID19 service guidelines have been promulgated, implementation data is yet unavailable. We performed a comprehensive audit of the implementation of services in a clinical oncology department. METHODS AND MATERIALS: A departmental protocol of priority-based treatment guidance was developed and a departmental staff rotation policy was implemented. Data was collected for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
432
1
15

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 469 publications
(482 citation statements)
references
References 13 publications
7
432
1
15
Order By: Relevance
“…A modeling study that analyzed the impact of delayed cancer surgery as a result of the COVID-19 pandemic reported that a three-month and six-month delay of surgery decreased the anticipated life-years gain after surgery by 19% and 43%, respectively. 23 Moreover, the impact was greater among patients with lung cancer. A dilemma occurs when elective surgeries are postponed in adherence to physical distancing and reorganization of healthcare resources because it contradicts the goal of minimizing delay of curative surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…A modeling study that analyzed the impact of delayed cancer surgery as a result of the COVID-19 pandemic reported that a three-month and six-month delay of surgery decreased the anticipated life-years gain after surgery by 19% and 43%, respectively. 23 Moreover, the impact was greater among patients with lung cancer. A dilemma occurs when elective surgeries are postponed in adherence to physical distancing and reorganization of healthcare resources because it contradicts the goal of minimizing delay of curative surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…Anticancer therapy or surgery was postponed or canceled. A modeling study that analyzed the impact of delayed cancer surgery due to the COVID-19 pandemic reported that a three-month and six-month delay of surgery decreased the anticipated life-years gain after surgery by 19 and 43%, respectively [ 23 ]. Moreover, the impact was greater among patients with lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…While deliberate postponement of "non-essential" procedures would be intuitive in the onset of any major outbreak, this approach is not sustainable in a protracted pandemic. The negative impact of pandemic-related treatment delays on COVID-free patients are increasingly being recognized [10][11][12], and poses many challenges for the post-pandemic recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the pandemic, IR services needed to balance between infection risk and resource optimization, against the delay of care for COVID-free patients [10][11][12]. Guidelines for procedural prioritization and acceptable delays such as the Procedure Acuity Scale (IR-PAS), by The Society of Intervention Radiology [13], which was adapted from the American College of Surgeons Elective Surgery Acuity Scale, were developed [14].…”
Section: Introductionmentioning
confidence: 99%